Micro-porous polyurethane damping pad for ballast bed and preparation method thereof

CN117604833BActive Publication Date: 2026-10-09BEIJING JIUZHOUYIGUI SHOCK & VIBRATION ISOLATION +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311656463.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-11-07
Filing Date
2023-12-05
Publication Date
2026-10-09
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

[0003]减振垫按照材质主要分为橡胶和聚氨酯两大类,橡胶减振垫荷载位移曲线呈激增特性,动静刚度比大,不利于隔振,且回弹性一般、抗氧化和抗紫外线性能差,易老化变脆;聚氨酯减振垫材料在恒定载荷工作区间呈近似线性变形,抵抗紫外线及臭氧能力强,不易老化,使用寿命长,有30年以上的应用业绩,减振效果保持良好,但是现有聚氨酯减振垫均为开孔结构,吸水后减振性能降低,因此需要开发一款具有合适刚度、低压缩变形,低动静比、低吸水率的微孔聚氨酯减振垫

Benefits of technology

[0019] Compared to existing technologies, the vibration damping pad described in this invention can achieve beneficial technical effects. For example, by simultaneously using PTMG1000 and PTMG1300 raw materials in appropriate proportions as the soft segment of the polyurethane material, the microporous polyurethane vibration damping pad has a low dynamic-to-static ratio, ensuring low dynamic stiffness when the train passes, thus achieving excellent vibration damping effect. The selection of appropriate soft and hard segment materials and proportions gives the vibration damping pad good resistance to compression and creep. For example, using polypropylene glycol (PPG2000) and castor oil as the soft segment of the polyurethane material gives the vibration damping pad excellent resistance to hydrolysis. Simultaneously, the addition of a water-repellent agent effectively prevents moisture from penetrating the material, resulting in a low water absorption rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117604833B_ABST
    Figure CN117604833B_ABST
Patent Text Reader

Abstract

The application discloses a kind of microcellular polyurethane shock pad for macadam bed and preparation method, including: microcellular polyurethane elastomer layer (10) and the geotextile layer (20) of microcellular polyurethane elastomer layer (10) side setting.It is good to resist compression, creep performance, damping performance and excellent hydrolysis resistance as the microcellular polyurethane shock pad for macadam bed and shock pad.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of vibration control technology for rail transit, specifically relating to a microporous polyurethane vibration damping pad for crushed stone track bed and its preparation method. Background Technology

[0002] In addition to using monolithic track beds on main lines, urban rail transit systems often employ crushed stone track beds in some surface sections, the throat areas of depots, and test tracks. Vibration problems are particularly severe in the throat areas outside depots, where numerous turnouts and crossovers exist. This vibration can affect the usability of superstructures and people's daily lives, becoming a significant obstacle to urban rail transit construction and commercial investment. Vibration damping pads, as a vibration reduction and isolation measure that effectively reduces the transmission of train wheel-rail vibrations outward, are currently widely used for vibration control in the outer areas of depots.

[0003] Vibration damping pads are mainly divided into two categories according to their materials: rubber and polyurethane. Rubber vibration damping pads exhibit a rapid increase in load-displacement curves, have a high dynamic-to-static stiffness ratio, which is not conducive to vibration isolation. They also have poor resilience, oxidation resistance, and UV resistance, and are prone to aging and becoming brittle. Polyurethane vibration damping pads, on the other hand, exhibit near-linear deformation in the constant load operating range, have strong resistance to UV rays and ozone, are not prone to aging, have a long service life, and have been used for more than 30 years with good vibration damping performance. However, existing polyurethane vibration damping pads are all open-cell structures, and their vibration damping performance decreases after absorbing water. Therefore, it is necessary to develop a microporous polyurethane vibration damping pad with suitable stiffness, low compression deformation, low dynamic-to-static stiffness ratio, and low water absorption rate.

[0004] Therefore, new technologies and materials are needed to at least partially eliminate the problems present in existing technologies. Summary of the Invention

[0005] Therefore, the present invention provides a microporous polyurethane vibration damping pad for crushed stone track bed and its preparation method. As a vibration damping pad, it has good heat insulation and flame retardant properties, tensile strength and vibration damping performance, and can at least partially eliminate the shortcomings of the prior art.

[0006] More specifically, according to one aspect of the present invention, a microporous polyurethane vibration damping pad for crushed stone roadbed is provided, comprising: a microporous polyurethane elastomer layer (10) and a geotextile layer (20) disposed on one side of the microporous polyurethane elastomer layer (10).

[0007] According to an embodiment of the present invention, the thickness of the geotextile layer (20) is 0.5 to 2 mm.

[0008] According to an embodiment of the present invention, the thickness of the microporous polyurethane elastomer layer (10) is 12 to 37 mm.

[0009] According to an embodiment of the present invention, the method for preparing the microporous polyurethane elastomer includes:

[0010] 1) Preparation of component A, comprising reacting 35-50 parts by weight of polytetrahydrofuran diol, 5-10 parts by weight of castor oil, 45-70 parts by weight of polyether polyol, 1-3 parts by weight of chain extender, 0.1-0.5 parts by weight of first catalyst and about 0.1-0.3 parts by weight of second catalyst to prepare component A;

[0011] 2) Preparation of component B, including reacting 100-200 parts by weight of modified MDI, 30-50 parts by weight of polypropylene glycol, and 50-80 parts by weight of polytetrahydrofuran glycol to prepare component B; and

[0012] 3) Heat components A and B to 50-60℃ respectively, mix them together, and react for 20-30 minutes to obtain microporous polyurethane elastomer, wherein the ratio of component A to component B is 100:45-55.

[0013] According to an embodiment of the present invention, the method for preparing the vibration damping pad includes: laying geotextile in the lower mold of the mold, then injecting component A and component B from step 3) into the mold at a temperature controlled at 45-50°C for reaction, and then closing the mold for curing for 10-20 minutes.

[0014] According to an embodiment of the present invention, the method for preparing the vibration damping pad further includes placing the cured vibration damping pad into an oven for post-curing treatment at a temperature of 50-80°C for 1-2 hours.

[0015] According to an embodiment of the present invention, the step of preparing component A further includes adding about 0.5 to 1 part by weight of a hydrophobic agent.

[0016] According to an embodiment of the present invention, the step of preparing component A further includes adding about 0.2 to 1 part by weight of ultraviolet absorber, 0.1 to 0.3 parts by weight of foam stabilizer, 1 to 3 parts by weight of water, 2 to 5 parts by weight of pore opener, 0.1 to 0.5 parts by weight of bactericide and mildew inhibitor, and 0.5 to 1 part by weight of color paste.

[0017] According to an embodiment of the present invention, in the step of preparing component A, the polytetrahydrofuran diol is PTMG1300 and the polyether polyol is POP36 / 28; in the step of preparing component B, the polypropylene oxide diol is PPG2000 and the polytetrahydrofuran diol is PTMG1000.

[0018] According to an embodiment of the present invention, the compression set of the vibration damping pad is less than 5%, preferably less than 2%, the resilience is greater than 50%, preferably greater than 60%, more preferably greater than 70%, the dynamic-to-static ratio is less than 1.3, the water absorption rate is not greater than 1.5%, preferably not greater than 1%, and the change rate of static foundation modulus after 10 million fatigue tests does not exceed 8%, preferably not greater than 6%.

[0019] Compared to existing technologies, the vibration damping pad described in this invention can achieve beneficial technical effects. For example, by simultaneously using PTMG1000 and PTMG1300 raw materials in appropriate proportions as the soft segment of the polyurethane material, the microporous polyurethane vibration damping pad has a low dynamic-to-static ratio, ensuring low dynamic stiffness when the train passes, thus achieving excellent vibration damping effect. The selection of appropriate soft and hard segment materials and proportions gives the vibration damping pad good resistance to compression and creep. For example, using polypropylene glycol (PPG2000) and castor oil as the soft segment of the polyurethane material gives the vibration damping pad excellent resistance to hydrolysis. Simultaneously, the addition of a water-repellent agent effectively prevents moisture from penetrating the material, resulting in a low water absorption rate. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the structure of a microporous polyurethane vibration damping pad for crushed stone track bed according to an embodiment of the present invention. Detailed Implementation

[0021] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The content shown is intended to fully illustrate the content of the present invention, but is not intended to limit the present invention.

[0022] Figure 1 This is a schematic diagram of the structure of a microporous polyurethane vibration damping pad for crushed stone roadbed according to an embodiment of the present invention. As shown in the figure, the embodiment of the present invention provides a microporous polyurethane vibration damping pad for crushed stone roadbed, which may include a microporous polyurethane elastomer layer 10 and a geotextile layer 20 disposed on one side of the microporous polyurethane elastomer layer 10.

[0023] The microporous polyurethane elastomer layer 10 is made of polyurethane elastomer raw materials, and its thickness can be, for example, 12-37 mm, or can be specifically prepared according to needs. The geotextile layer 20 is a puncture-resistant geotextile, whose function is to protect the microporous polyurethane elastomer from damage under the local force of ballast particles and maintain the integrity of the microporous polyurethane elastomer.

[0024] Microporous polyurethane elastomers can be prepared by mixing and curing component A and component B. Component A is mainly prepared by mixing and reacting polytetrahydrofuran glycol (e.g., PTMG1300), castor oil, polyether polyol, chain extender, catalyst, foam stabilizer, water repellent, water, and colorant in a certain proportion. Component B is mainly prepared by mixing and reacting modified MDI (e.g., MM103C), polypropylene glycol (e.g., PPG2000), and polytetrahydrofuran glycol (e.g., PTMG1000).

[0025] Polytetrahydrofuran diol is a special polyether diol that can be used in high-performance water-resistant polyurethane elastomers. In this invention, PTMG1000 and PTGM1300 are selected as raw materials, and polyurethane elastomers with suitable modulus and strength are prepared by different ratios and amounts. When PTMG1000 and PTGM1300 are used as soft segments, their molecular chain structure is relatively regular, and physical cross-linking points are easily formed between molecules, and they contain a large number of ether bonds. Experimental studies have shown that when these two polyether polyols are used as raw materials, the polyurethane elastomer can have good low-temperature performance, wear resistance, aging resistance, and mildew resistance, while also having good flexibility and elasticity. Under dynamic load conditions, the soft segment molecular chains connected to the hard segments can easily reciprocate near the equilibrium position, resulting in a fast stress response and thus a low dynamic-to-static ratio.

[0026] Pure MDI is inconvenient to store, and repeated heating can affect its quality. Modified MDI solves this storage problem. Modified MDI constitutes the hard segments of polyurethane, and the benzene rings in its molecular chain provide rigidity. Compared to TDI and PAPI, the hard segments formed by MDI are the most regularly arranged and easily crystallize into the crystal lattice. At the same hard segment content, MDI forms a relatively larger number of hydrogen bonds, resulting in greater strength. Experiments have shown that the hard segment content significantly affects the stiffness of polyurethane elastomers. To produce samples with acceptable stiffness, the proportion of hard segments, i.e., the content of modified MDI, must be controlled.

[0027] Castor oil is a type of vegetable oil containing hydroxyl groups and carbon-carbon double bonds, with ricinoleic acid triglyceride as its main component. Studies have found that castor oil, when used as a soft segment in polyurethane, can improve mechanical properties. The nonpolar fatty acid chains and carbon-carbon double bonds in its molecule give it good water resistance and endow polyurethane with good flexibility and low-temperature performance.

[0028] Polypropylene glycol can increase the flexibility of polyurethane and increase the elongation at break. After testing, polypropylene glycol with a molecular weight of 2000 (PPG2000) was selected, which can effectively reduce the cost of raw materials while ensuring the material performance.

[0029] Polyether polyols (POP36 / 28) are polymeric polyols containing rigid styrene, acrylonitrile homopolymers and copolymers and graft polymers. These vinyl polymers act as organic "fillers" to provide rigidity to polyurethane foams.

[0030] Experiments have verified that using polypropylene glycol, castor oil polyol, polytetrahydrofuran glycol, and polyether polyol in a certain proportion as the soft segment material of polyurethane can give the elastomer suitable stiffness, low dynamic-to-static ratio, low compression creep, and low water absorption.

[0031] The preparation process of the present invention will be further described below with reference to specific embodiments.

[0032] Example 1

[0033] (1) Preparation of component A

[0034] a. Place polytetrahydrofuran diol (PTMG1300, Mitsubishi Chemical Corporation, Japan) in an oven and heat at 80°C (70-90°C) for 3 hours (2-4 hours) until liquefied.

[0035] b. 40 parts by weight of polytetrahydrofuran diol (PTMG1300, Mitsubishi Chemical Corporation, Japan), 60 parts by weight of polyether polyol (POP36 / 28) (Shandong Lanxing Dongda Chemical Industry Co., Ltd.), 8 parts by weight of castor oil (Vertellus), 1 part by weight of chain extender 6200 (Mitsubishi Chemical Corporation, Japan), 0.3 parts by weight of the first catalyst, organotin catalyst T120 (Shule Industrial (Shanghai) Co., Ltd.), 0.2 parts by weight of the second catalyst, A33 (Changzhou Kerry Chemical Technology Co., Ltd.), and 0.2 parts by weight of... Add the following ingredients by weight: foaming agent B8905 (Evonik Specialty Chemicals (Shanghai) Co., Ltd.), 0.3 parts by weight of bactericide and mildew inhibitor BBIT (Arch, Inc., USA), 0.8 parts by weight of water repellent (Shanghai Kaiyin Chemical Co., Ltd.), 3 parts by weight of cell opener CJ-170 (Shanghai Gaoqiao Petrochemical Co., Ltd.), 0.6 parts by weight of ultraviolet absorber UV1 (Kunshan Zhongxing Dyestuff Chemical Co., Ltd.), 2 parts by weight of distilled water, and 0.6 parts by weight of color paste 076 (Insino Chemical (Shanghai) Co., Ltd.) to the reactor and close the valve.

[0036] c. Raise the temperature of the reactor to 65℃ (50-75℃), stir and mix at 100 rpm (50-130 rpm) for 2 hours (2-3 hours);

[0037] d. Next, test the viscosity, moisture content, and hydroxyl value. Once the standards are met, package the product for later use. The specific testing and standards are as follows: Rotational viscometer DV2T, Brookfield Instruments, USA, viscosity ≤4000mPa.S; Karl Fischer moisture analyzer V10S, Mettler V10S, moisture content <0.5%; Hydroxyl value: Fourier transform near-infrared spectrometer, MB3600-CH20, ABB, 20-50mgKOH / g.

[0038] (2) Preparation of component B

[0039] a. Place polypropylene glycol (PPG2000) in an oven and heat at 95℃ (80~100℃) for 4 hours (3~6h) until liquefied.

[0040] b. Add 40 parts by weight of polypropylene glycol (PPG2000) (Mitsubishi Chemical Corporation, Japan) to the reactor, start the heating device, set the temperature to 100°C, start the stirrer to stir at 100 rpm (80-130 rpm), when the temperature reaches 100°C, start the vacuum pump to evacuate the vacuum for 2 hours (2-3 hours).

[0041] c. Take a small sample to test the moisture content (Karl Fischer moisture analyzer, V10S Mettler, moisture content <0.1%). After the sample meets the standard, cool the reactor to 55℃ (50-60℃).

[0042] d. Slowly add 150 parts by weight of modified MDI-diphenylmethane diisocyanate (Yantai Wanhua Polyurethane Co., Ltd., MM103C) and 100 parts by weight of polytetrahydrofuran diol PTMG1000 (Mitsubishi Chemical Corporation, Japan), and continue stirring and mixing for 5 hours (4-6 hours). Take a sample to test the NCO content (Fourier transform near-infrared spectrometer, MB3600-CH20 type, ABB, NCO 5-15%).

[0043] e. Once the target is met, the reactor should be cooled to room temperature, stirring stopped, and the vessel sealed for later use.

[0044] (3) Preparation of microporous polyurethane elastomer vibration damping pads

[0045] a. Add component A to the component A raw material tank of the polyurethane foam casting machine, start stirring, heat to 55℃ (50~60℃), and keep at the temperature for 1 hour (1~2h);

[0046] b. Add component B to the component B raw material tank of the polyurethane foam casting machine, start stirring, heat to 55℃ (50~60℃), and keep at the temperature for 1.5 hours (1~2h);

[0047] c. Clean the mold, apply release agent, and control the mold temperature at 50℃ (45~50℃);

[0048] d. Lay a layer of geotextile on the lower mold;

[0049] e. Start the polyurethane foam casting machine, set the ratio of component A to component B to A:B = 100:50, adjust the casting speed to 200g / s (50~400g / s), calibrate the casting time to 15s, pour the material into the mold according to the above conditions, and close the mold.

[0050] f. Close the mold and cure for 20 minutes;

[0051] g. Open the mold, take out the polyurethane elastomer product, trim the edges, and put the pad into the oven for post-curing treatment at 65℃ for 2 hours.

[0052] h. After being removed, the material is naturally dried to room temperature to obtain the microporous polyurethane vibration damping pad for crushed stone track bed of Example 1, which is then sealed and stored for later use.

[0053] Comparative Example 1

[0054] Except that PTMG1300 is not included in the preparation of component A, the rest is the same as in Example 1.

[0055] Comparative Example 2

[0056] Except that PTMG1000 is not included in the preparation of component B, the rest is the same as in Example 1.

[0057] Comparative Example 3

[0058] Except for the reduced proportion of modified MDI in component B, the rest is the same as in Example 1.

[0059] Comparative Example 4

[0060] Except for the increased proportion of modified MDI in component B, the rest is the same as in Example 1.

[0061] Comparative Example 5

[0062] Except that the preparation of component B does not contain PTMG2000, the rest is the same as in Example 1.

[0063] Comparative Example 6

[0064] Except that castor oil is not included in the preparation of component A, the rest is the same as in Example 1.

[0065] Comparative Example 7

[0066] Except that the preparation of component A does not contain a hydrophobic agent, the rest is the same as in Example 1.

[0067] The formulations of Example 1 and Comparative Examples 1-7 are shown in Table 1 below:

[0068] Table 1: Recipe Table for Each Example

[0069]

[0070]

[0071] According to the relevant testing standards, the material's density, compressive strength, tensile properties, water absorption, stiffness, and other properties were tested. The testing standards and results are as follows.

[0072] Testing standards:

[0073] Product Performance

[0074] Density: 200~300kg / m3 GB / T 6343-2009

[0075] Tensile strength: ≥0.5MPa GB / T 10654-2001

[0076] Elongation at break: ≥150% GB / T 10654-2001

[0077] Compression set: ≤5% GB / T 10653-2001

[0078] Resilience: ≥50% GB / T 10652-2001

[0079] Water absorption rate: ≤1% GB / T 1690-2006

[0080] Hot air aging performance: Tensile strength change rate ≤5%; Elongation at break change rate ≤10% GB / T3512-2014

[0081] Liquid resistance: Tensile strength change rate ≤5%; Elongation at break change rate ≤10% GB / T1690-2010

[0082] Static foundation modulus: 0.015~0.025 N / mm3 GB / T 39705-2020

[0083] Dynamic-to-static ratio: <1.3 GB / T 39705-2020

[0084] Fatigue performance, thickness variation rate ≤3%, static foundation modulus variation rate ≤10%, GB / T 39705-2020

[0085] Table 2: Test Results

[0086]

[0087] Experimental results show that the products prepared by this invention using specific raw materials and proportions fully meet or even far exceed the requirements of relevant standards, and have good compression resistance, creep resistance, vibration damping performance, and excellent hydrolysis resistance.

[0088] The above description of the embodiments is intended to enable those skilled in the art to understand and apply the present invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the embodiments described herein, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A microporous polyurethane vibration damping pad for crushed stone track bed, comprising: Microporous polyurethane elastomer layer (10) and geotextile layer (20) disposed on one side of microporous polyurethane elastomer layer (10); The preparation methods of microporous polyurethane elastomers include: 1) Preparation of component A, comprising reacting 35-50 parts by weight of polytetrahydrofuran diol, 5-10 parts by weight of castor oil, 45-70 parts by weight of polyether polyol, 1-3 parts by weight of chain extender, 0.1-0.5 parts by weight of first catalyst and 0.1-0.3 parts by weight of second catalyst to prepare component A; 2) Preparation of component B, including reacting 100-200 parts by weight of modified MDI, 30-50 parts by weight of polypropylene glycol, and 50-80 parts by weight of polytetrahydrofuran glycol to prepare component B; and 3) Heat components A and B to 50-60℃ respectively, mix them together, and react for 20-30 minutes to obtain microporous polyurethane elastomer, wherein the ratio of component A to component B is 100:45-55; In the step of preparing component A, the polytetrahydrofuran diol is PTMG1300 and the polyether polyol is POP36 / 28; in the step of preparing component B, the polyoxypropylene diol is PPG2000 and the polytetrahydrofuran diol is PTMG1000. The step of preparing component A also includes adding 0.5 to 1 part by weight of a hydrophobic agent.

2. The microporous polyurethane vibration damping pad for crushed stone track bed as described in claim 1, characterized in that: The thickness of the geotextile layer (20) is 0.5 to 2 mm.

3. The microporous polyurethane vibration damping pad for crushed stone track bed as described in claim 2, characterized in that: The thickness of the microporous polyurethane elastomer layer (10) is 12-37 mm.

4. The microporous polyurethane vibration damping pad for crushed stone track bed as described in claim 1, characterized in that: The method for preparing the vibration damping pad includes: laying geotextile in the lower mold, then injecting component A and component B from step 3) into the mold at a temperature controlled at 45-50°C for reaction, and then closing the mold for curing for 10-20 minutes.

5. The microporous polyurethane vibration damping pad for crushed stone track bed as described in claim 4, characterized in that: The method for preparing the vibration damping pad also includes placing the cured vibration damping pad into an oven for post-curing treatment at a temperature of 50-80℃ for 1-2 hours.

6. The microporous polyurethane vibration damping pad for crushed stone track bed as described in claim 1, characterized in that: The step of preparing component A also includes adding 0.2 to 1 part by weight of ultraviolet absorber, 0.1 to 0.3 parts by weight of foam stabilizer, 1 to 3 parts by weight of water, 2 to 5 parts by weight of pore opener, 0.1 to 0.5 parts by weight of bactericide and mildew inhibitor, and 0.5 to 1 part by weight of color paste.

7. The microporous polyurethane vibration damping pad for crushed stone track bed as described in claim 1, characterized in that: The vibration damping pad has a compression permanent deformation of less than 5%, a resilience of more than 50%, a dynamic-to-static ratio of less than 1.3, a water absorption rate of no more than 1.5%, and a static foundation modulus change rate of no more than 8% after 10 million fatigue tests.

Citation Information

Patent Citations

  • Polyurethane flexible foam material for railway curing ballast bed and preparation method thereof

    CN112920377A

  • Low-density fatigue-resistant microporous polyurethane elastic anti-vibration pad and preparation method thereof

    CN113563563A

  • Elasticity subtracts shock insulation board

    CN205100030U